FAKTOR DETERMINAN YANG MEMPENGARUHI KEJADIAN STUNTING PADA SISWA KELAS 1 USIA 6-7 TAHUN DI SDN 1 TANJUNGSARI KECAMATAN ROWOSARI KABUPATEN KENDAL - Hasanah, Nur; Maryanto, Sugeng (UNIVERSITAS NGUDI WALUYO, 2013)
In Indonesia, the prevalence of stunting among school children is still high as a result of inadequate nutritional intake. Stunting is a public health concern due to the increased risk of morbidity, mortality, delayed motor development, and delayed linear growth or height. The purpose of this study was to determine the relation between energy intake, age birth, birth weight, and infectious diseases with stunting incidences on first grode students of aged 6-7 years old at Tanjungsari 1 elementary school. The design of this study was analytic with cross sectional correlation. The population in this study was grade one students at Tanjungsari 1 elementary school. the Samples were to 33 students aged 6-7 years old with a total sampling technique sampling. Data Collecting used interview techniques by using a 24-hour food recall method to determine energy intake and using interviews with questionnaires to determine the age of birth, birth weight, and infectious diseases. The data analysis technique used Kendall Tau test. The results showed that energy intake had a positive correlation test (p = 0.006), there was a correlation with the incidences of stunting. Age birth had a positive correlation test (p = 0.005), there was a correlation with the incidences of stunting. Birth weight had a weak correlation test (p = 0.111), there was no association with the incidences of stunting. Infectious diseases had a positive correlation test (p = 0.001), there was a correlation with the incidences of stunting. It was concluded that there was a relation between energy intake, age birth, and the infectious diseases with stunting incidences. There was no relation between the birth weight with stunting incidences Abtrak : Di Indonesia, prevalensi stunting pada anak sekolah masih cukup tinggi sebagai akibat asupan gizi yang tidak adekuat. Stunting merupakan masalah kesehatan masyarakat karena berhubungan dengan meningkatnya risiko terjadinya kesakitan, kematian, perkembangan motorik terhambat, dan terhambatnya pertumbuhan linier atau tinggi badan. Tujuan penelitian ini adalah mengetahui hubungan antara asupan energi, umur kelahiran, berat badan lahir, dan penyakit infeksi dengan kejadian stunting pada siswa kelas 1 usia 6-7 tahun di SDN 1 Tanjungsari. Rancangan penelitian ini adalah analitik korelasi dengan pendekatan cross sectional. Populasi pada penelitian ini adalah siswa kelas 1 di SDN 1 Tanjungsari. Sampel yang di ambil sebanyak 33 siswa usia 6-7 tahun dengan teknik pengambilan total sampling. Pengumpulan data menggunakan teknik wawancara dengan menggunakan metode food recall 24 jam untuk mengetahui asupan energi dan menggunakan teknik wawancara dengan kuesioner untuk mengetahui umur kelahiran, berat badan lahir, dan penyakit infeksi. Teknik analisis data yang digunakan adalah uji Kendall Tau. Hasil penelitian menunjukkan bahwa ada hubungan antara asupan energi, umur kelahiran, dan penyakit infeksi dengan kejadian stunting. Tidak ada hubungan antara berat badan lahir dengan kejadian stunting. Disimpulkan bahwa ada hubungan antara asupan energi, umur kelahiran, dan penyakit infeksi dengan kejadian stunting. Tidak ada hubungan antara berat badan lahir dengan kejadian stunting.